Faktor-Faktor yang Mempengaruhi Kualitas Audit dengan Independensi Auditor sebagai Moderasi - Alviani, Anita Wahyu; Rahman, Taufikur (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2021)
This study aims to determine the effect auditors competence, objectivity, religiosity to audit quality with auditors independence as the moderating variable of the auditors of Inspektorat Kabupaten Wonogiri, Semarang, dan Kota Salatiga. The analitycal methods used are the research instrument test, descriptive statistical test, multiple regression test, T test, F test, R2, classical assumption test, and MRA. The data was processed using IBM Statistics SPSS version 23. The results showed that the auditors competence variable had no effect on audit quality. The objectivity variable partially has a positive and significant effect on audit quality. The religiosity variable partially has a positive and significant effect on audit quality.The result of the MRA test indicate that auditor independence can moderate the effect of auditor competence, objectivity, and feligiosity on audit quality.